Effects of initial eutting time and nitrogen fertilization in dry matter yields and quality of Digitaria eriantha Steudel subsp. eriantha ev. Irene. (Semiárida, 2020)
Digitaria eriantha Steudel subsp. eriantha is a perennial forage grass originated from Africa, characterized by its productivity and quality. The trial was done close to V. Mercedes of 3 cutting strategies (at flag leaf, first mature panicles and end of the growing stage) and 2 different nitrogen fertilization levels (0 and 127 kgN2/ha) on dry matter (OM) yield, crude protein and in vitro digestibility. The highest yields (P
Keywords: Digitaria eriantha; smuts finger grass; dry matter yields; defoliation; fertilization; quality